Duodenal bulb plasma cells in duodenitis and duodenal ulceration. Issue 10 (October 1985) - Scott, B B; Goodall, A; Stephenson, P; Jenkins, D
Abstract : Using an immunoperoxidase technique IgA, IgM, IgE and IgG plasma cells were studied in endoscopic duodenal bulb biopsies taken from 14 controls, 25 patients with grade 1 duodenitis (Whitehead classification), 12 patients with grade 2 duodenitis and three with grade 3 duodenitis. The control counts were compared with those in the jejunum and rectum. In addition cell counts were compared in 16 pairs of patients, with and without duodenal ulcer, exactly matched for grade of duodenitis. The control counts were not significantly different from counts in jejunum or rectum except for IgG which were higher in the jejunum (p = 0.03). IgA plasma cell counts were significantly increased in both grade 1 and grade 2 duodenitis compared with controls (p less than 0.05 and p less than 0.01). There was no significant difference for the other plasma cells. All plasma cell counts were decreased in the small group of grade 3 duodenitis compared with the other groups. There was no significant difference between counts in duodenitis whether or not there was associated duodenal ulceration. The isolated IgA plasma cell response of the duodenal bulb mucosa in duodenitis is very different from that of the jejunal mucosa in coeliac disease, and the rectal mucosa in inflammatory bowel disease and bacterial colitis and probably represents the basic response to any mucosal damage.